2022
DOI: 10.3389/fgene.2022.1046192
|View full text |Cite
|
Sign up to set email alerts
|

Applying multi-omics data to study the genetic background of bovine respiratory disease infection in feedlot crossbred cattle

Abstract: Bovine respiratory disease (BRD) is the most common and costly infectious disease affecting the wellbeing and productivity of beef cattle in North America. BRD is a complex disease whose development is dependent on environmental factors and host genetics. Due to the polymicrobial nature of BRD, our understanding of the genetic and molecular mechanisms underlying the disease is still limited. This knowledge would augment the development of better genetic/genomic selection strategies and more accurate diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 72 publications
6
8
0
Order By: Relevance
“…Further, some of the differentially methylated genes ( TGM3, NRG1, RETN, IL1R2, ADGRE1, ALPL, KREMEN1, TRPC5, MN1, ALOX5AP, DYSF, ITGA9, NUPR1, SLC28A3, IGLON5, PTPN5, GLT1D1, DPYS, WIPI1, CFB, LOC511106, IL3RA ) also overlapped with previously identified differentially expressed genes in studies of BRD susceptibility of pre-weaned calves and feedlot cattle [43, 65]. Of these, NUPR1, CFB and ADGRE1 were also associated with identified trans-eQTLs [43].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Further, some of the differentially methylated genes ( TGM3, NRG1, RETN, IL1R2, ADGRE1, ALPL, KREMEN1, TRPC5, MN1, ALOX5AP, DYSF, ITGA9, NUPR1, SLC28A3, IGLON5, PTPN5, GLT1D1, DPYS, WIPI1, CFB, LOC511106, IL3RA ) also overlapped with previously identified differentially expressed genes in studies of BRD susceptibility of pre-weaned calves and feedlot cattle [43, 65]. Of these, NUPR1, CFB and ADGRE1 were also associated with identified trans-eQTLs [43].…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, epigenetic changes may also play a role since a significant number of genes have been identified in this study as differentially methylated between healthy calves and those diagnosed with BRD. Although we have not generated RNA-Sequencing data from these calves to compare their blood transcriptomic profiles, when we compared our results with the results of previous transcriptomics, eQTL and genome-wide association (GWAS) studies many of the differentially methylated genes have been also identified and prioritised as good candidate genes for BRD resistance in these studies [43, 65]. Specifically, eight genes ( KPNA6, NEIL3, ADCK1, ZNF507, REEP3, AHSA1, SEPTIN11 and IgLON5) identified as differentially methylated were also identified within significant GWAS windows in the study of BRD susceptibility in pre-weaned Holstein calves [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our objective in this study was to identify differences in gene expression and associated host-driven biological systems that may be impacted by marketing decisions and how these influence eventual BRD morbidity after backgrounding arrival, in order to explore potential mechanisms of BRD development or resistance that may be leveraged in future studies. While both our research group and others have used the blood RNA-Seq methodology to identify potential predictive markers and mechanisms related to BRD [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], this study, to our knowledge, is one of the first to utilize said technologies to evaluate how marketing decisions, with relationship to BRD, influence inflammatory- and immune-mediated mechanisms in cattle. Importantly, exposure to an auction market setting and an order-buyer facility for only three days was associated with the differential expression of 2961 genes representing 113 biological processes.…”
Section: Discussionmentioning
confidence: 99%